The Role of the Surveyor in Discharge Planning for Patient Safety - Hisnindarsyah; Ahyar Wahyudi; Buyung Nazeli; Listyo Yuwanto; Arif Hidayatullah (Formosa Journal of Science and Technology, 2023)
This article reviews the critical process of patient discharge from hospitals and its challenges, with a focus on the length of stay (LOS) as an indicator of therapeutic success and treatment costs. Emphasis is placed on the importance of accurate diagnosis, appropriate discharge planning, and the prevention of readmissions to the hospital. Utilising the Calgary Family System Theory (CSFT) and the concept of Person-Centered Care (PCC), this piece underscores the significance of an individualised approach, patient involvement in decision-making, effective communication, and multidisciplinary collaboration in the discharge process. Thus, effective discharge planning can enhance the quality of patient care and reduce the economic burden associated with patient readmissions.